The humble sublime: secularity and the politics of belief = secularity and the politics of belief - Thiemann, Ronald F. (I.B. Tauris, 2014)
Biographical Note -- Introduction -- 1. Sacramental Realism: The Humble Sublime -- 2. Sacramental Poetry as Memory and Witness: Anna Akhmatova -- 3. Realism as Resistance and Reversal: Langston Hughes -- 4. Humanity Without God: Faith without Illusions: George Orwell -- 5. A Strange Form of Love: Realist Hope and Rebellious Politics: Albert Camus -- 6. Conclusion / Mara Willard and Paul Dafydd Jones